Tinjauan Maslahah Mursalah terhadap Pencatatan Hibah Aset Berharga - Agnia Ruslani Muftin; Nandang Ihwanudin; Popon Srisulawati (Bandung Conference Series: Sharia Economic Law, 2024)
Abstract. In Cangkuan District, Bandung Regency, the grant process is carried out at the KUA Office, which provides a place only for implementing grant contracts. The legal basis for grants refers to the provisions in KHI and KHES. The practice of giving is often characterized by the withdrawal of gifts by givers for various reasons, such as urgent needs or an increase in the value of the objects donated. The research uses the action case study method to reveal the grant process and practice of recording valuable assets in Cangkuan District. The research results show that lack of recording of grants can lead to disputes, and although there is no text provision, the maslahah murlah method suggests the need for recording to avoid potential conflicts in the future. Abstrak. Di Kecamatan Cangkuan, Kabupaten Bandung, proses hibah dilakukan di Kantor KUA, yang menyediakan tempat hanya untuk pelaksanaan akad hibah. Dasar hukum hibah mengacu pada ketetapan dalam KHI dan KHES. Praktik hibah seringkali diwarnai oleh penarikan kembali hibah oleh para pemberi dengan berbagai alasan, seperti kebutuhan mendesak atau kenaikan nilai benda yang dihibahkan. Penelitian menggunakan metode studi kasus tindakan untuk mengungkapkan proses hibah dan praktik pencatatan aset berharga di Kecamatan Cangkuan. Hasil penelitian menunjukkan bahwa kekurangan pencatatan hibah dapat menyebabkan sengketa, dan meskipun tidak ada ketentuan nash, metode maslahah mursalah menyarankan perlunya pencatatan untuk menghindari potensi konflik di masa depan.